Engineering Properties of Some Basement Rocks of Nigeria as Aggregate in Civil Engineering Pavement Construction - Olusola, Falowo Olumuyiwa (Asian Review of Environmental and Earth Sciences, 2019)
The engineering performance of construction materials is strongly related to their physical properties. Therefore in order to determine the suitability of the rock units in northern parts of Ondo State, Nigeria as aggregates for pavement construction, eight rock samples comprising porphyritic granite, granite, migmatite, granite gneiss, quartz schist, granodiorite, charnockite, and quartzite, were subjected to physical tests which include moisture content, dry density, porosity, specific gravity, aggregate impact value, aggregate crushing value, point load strength index, unconfined compressive strength, and shear strength. The tests were conducted in accordance to ASTM D2216 and ISRM-2386 standard test methods. The aggregate impact value of the samples ranges from 11.2 (Quartzite/granite gneiss) to 17.3 (Charnockite), while aggregate crushing value varies from 18.4 (Quartzite) to 25.2 (Charnockite). The water absorption of the rock units ranges between 0.27 and 0.82%, and porosity recorded 0.18 – 0.46%. Point load strength index, shear strength, and unconfined compressive strength of the samples ranges from 7.40 - 9.87, 60.5 – 92.6MPa, and 121.1 – 185.3 respectively. The values of AIV and ACV are within the standard specification value for road material, cement concrete pavement and wearing surfaces of 30% and 45% maximum. Therefore the rock units are very excellent as aggregate for road pavement construction and categorized as strong aggregate in terms of quality for road pavement. It is also observed that porosity and specific gravity are the major parameters that show strong positive correlations (≥0.5) with important geotechnical parameters such as shear strength, unconfined compressive strength, and point load strength index.